What Do We Mean When We Say Intermediate City? Towards a Definition of an Intermediate City as a Mode of Life (Revista Iberoamericana de Estudios Municipales, 2024)
The notion of intermediate city has acquired great importance in recent years in Chile and Latin America. Although the reference to this notion is usually clear, what defines and distinguishes an intermediate city as such is much less clear. In this article, we examine different proposals for defining this concept. We note that absolute definitions of size, which are often used as operational definitions, are not adequate. In addition, definitions based on the role and location of these cities are more useful, but they too face difficulties. We conclude by suggesting that exploring possibilities provided by an approach that defends a definition based on the idea of way of life could be an interesting approach to define these cities.
Keywords: Intermediate city; way of life; urban; rural; territory